Dietary vitamin D interacts with high phosphate-induced cardiac remodeling in rats with normal renal function. Issue 3 (31st August 2019) - Hu, Ming Chang; Scanni, Roberto; Ye, Jianfeng; Zhang, Jianning; Shi, Mingjun; Maique, Jenny; Flores, Brianna; Moe, Orson W; Krapf, Reto
Abstract: Background: Vitamin D (VD) and phosphate (Pi) load are considered as contributors to cardiovascular disease in chronic kidney disease and the general population, but interactive effects of VD and Pi intake on the heart are not clearly illustrated. Methods: We fed normal male rats with three levels of dietary VD (100, 1100 or 5000 IU/kg chow) and Pi (0.2, 0.6 or 1.6%) (3X3 design) for 8 weeks and examined renal and cardiac function and histology. Results: High dietary Pi decreased plasma and renal Klotho and plasma 25-hydroxyvitamin D, and increased plasma Pi, fibroblast growth factor 23 and parathyroid hormone without affecting renal function, while low Pi increased plasma and renal Klotho. Both low and high VD diets enhanced high Pi-reduced Klotho expression. Low dietary VD reduced-plasma Klotho was rescued by a low Pi diet. High dietary Pi reduced-cardiac ejection fraction was not modified by a low or high VD diet, but the dietary VD effects on cardiac pathologic changes were more complex. High dietary Pi-induced cardiac hypertrophy was attenuated by a low VD and exacerbated by a high VD diet. In contrast, high dietary Pi -induced cardiac fibrosis was magnified by a low VD and attenuated by a high VD diet. Conclusions: High Pi diet induces hypertrophy and fibrosis in left ventricles, a low VD diet accelerates high Pi-induced fibrosis, and a high VD diet exacerbated high Pi -induced hypertrophy. Therefore, cardiac phosphotoxicity is exacerbated by either high or low dietary VD in rats with normal kidney function.